2018
DOI: 10.4314/njtd.v14i2.6
|View full text |Cite
|
Sign up to set email alerts
|

Empirically Determined Passenger Ferry Navigable Routes within Lagos Lagoon

Abstract: Hydrographic surveys define shorelines and depths of lakes, streams, oceans, reservoirs, and other bodies of water. Sea surveying is associated with port and offshore industries and the marine environment, including measurements and marine investigations made by ship-borne personnel. In addition, accurate measurement and modelling of hydrographic information is important to control waterways boat services with existing roadway transportation services. This paper attempts an empirical analysis of hydrographic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…Also, Chukwuma (2014); Bassey & Nsa (2018) noted that inadequate water transport facilities was a major factor impeding the development of inland water transport in Nigeria. In another vein, Ndikom, (2013) and Adejare et. al., (2017) focused on the neglect and undervalue of water transport in Lagos State, while the work of Edelman, (2015) concluded that the plan to integrate the Bus Rapid Transit (BRT) with light rail schemes may not solve the congestion problem in Lagos metropolis, except it also incorporates the water transport mode.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, Chukwuma (2014); Bassey & Nsa (2018) noted that inadequate water transport facilities was a major factor impeding the development of inland water transport in Nigeria. In another vein, Ndikom, (2013) and Adejare et. al., (2017) focused on the neglect and undervalue of water transport in Lagos State, while the work of Edelman, (2015) concluded that the plan to integrate the Bus Rapid Transit (BRT) with light rail schemes may not solve the congestion problem in Lagos metropolis, except it also incorporates the water transport mode.…”
Section: Introductionmentioning
confidence: 99%
“…In Oyadongha, (2014) ;Iheamnachor, (2014) and Akogun, (2014), they asserted that poor safety practices are perceived to be responsible for the high accident rate in water transport. Furthermore, studies by Adejare et al, (2017); Ogunbajo et al, (2017) and Ademiluyi et al, (2016) dwelled on the existing water transport facilities in terms of size and access to commuters in Lagos State. Also, Chukwuma (2014); Bassey & Nsa (2018) noted that inadequate water transport facilities was a major factor impeding the development of inland water transport in Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…Although, water transport is known to be comparatively cheaper and most efficient for riverine communities, this mode of transport is currently highly neglected and undervalued in the country (Ndikom, 2013;Adejare et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Lagos, the commercial capital of Nigeria has been observed to possess the necessary inland waterway network capacity to transport commuters to most parts of the city, but the waterways are grossly under utilized. The existing water transport facilities are inadequate both in terms of size and access to commuters (Adejare et al,2017;Ogunbajo et al, 2017). Ademiluyi et al, (2016) also observe that in spite of the numerous merits of water transport such as the low cost, larger capacity and safety, this mode of transport is yet to be fully tapped to achieve the potential benefits it possesses.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, understanding seafloor morphology and its evolution is critical to scientific investigations of boundary layer processes. Hydrographic survey supports a variety of marine functions: port and harbour maintenance (dredging), coastal engineering (subsidence assessments and restoration projects), coastal management and offshore resources development [20].…”
Section: Introductionmentioning
confidence: 99%